Soluble Recombinant Protein Production in Pseudoalteromonas haloplanktis TAC125: The Case Study of the Full-Length Human CDKL5 Protein - Calvanese M.; Colarusso A.; Lauro C.; Parrilli E.; Tutino M. L. (Humana Press Inc., 2022)
The Antarctic bacterium Pseudoalteromonas haloplanktis TAC125 is an unconventional protein production host displaying a notable proficiency in the soluble production of difficult proteins, especially of human origin. Furthermore, the accumulation of recombinant products in insoluble aggregates has never been observed in this bacterium, indicating that its cellular physicochemical conditions and/or folding processes are rather different from those observed in mesophilic bacteria. The ability of this cell factory was challenged by producing a human protein, the cyclin-dependent kinase-like 5 (hCDKL5) in the bacterium cytoplasm at 0 °C. Human CDKL5 is a serine/threonine protein kinase characterized by the absence of a defined structure for the last two/third of its sequence, one of the largest intrinsically disordered regions so far observed in a human protein. This large unstructured domain makes difficult its production in most of the conventional hosts since the recombinant product accumulates as insoluble aggregates and/or is heavily proteolyzed. As the full-length hCDKL5 production is of great interest both for basic science and as protein drug for an enzyme replacement therapy, its production in the Antarctic bacterium was tested by combining the use of a regulated psychrophilic gene expression system with the use of a defined growth medium optimized for the host growth at subzero temperature. This is the first report of soluble and full-length recombinant production of hCDKL5 protein in a bacterium.